2023
DOI: 10.1093/brain/awad048
|View full text |Cite
|
Sign up to set email alerts
|

Epileptogenesis in tuberous sclerosis complex-related developmental and epileptic encephalopathy

Abstract: Epileptogenesis in infants with tuberous sclerosis complex (TSC) is a gradual and dynamic process leading to early onset and difficult-to-treat seizures. Several cellular, molecular, and pathophysiologic mechanisms, including mammalian target of rapamycin (mTOR) dysregulation, GABAergic dysfunction, and abnormal connectivity, may play a role in this epileptogenic process, and may also contribute to the associated developmental encephalopathy. Disease specific antiseizure medications or drugs targeting the mTOR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 224 publications
0
14
0
Order By: Relevance
“…48 Treatment during the presymptomatic phase in tuberous sclerosis complex sets precedence for presymptomatic treatment in other developmental epilepsy disorders, like SWS, where a high percentage of patients will have seizure onset in the first few years of life, and where early age of seizure onset has been repeatedly associated with worse neurological and developmental outcome. [49][50][51] More studies are needed to establish that presymptomatic treatment improves long-term neurological and cognitive outcomes in SWS. In the meantime, however, these results strongly suggest that presymptomatic treatment can significantly delay seizure onset in these infants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…48 Treatment during the presymptomatic phase in tuberous sclerosis complex sets precedence for presymptomatic treatment in other developmental epilepsy disorders, like SWS, where a high percentage of patients will have seizure onset in the first few years of life, and where early age of seizure onset has been repeatedly associated with worse neurological and developmental outcome. [49][50][51] More studies are needed to establish that presymptomatic treatment improves long-term neurological and cognitive outcomes in SWS. In the meantime, however, these results strongly suggest that presymptomatic treatment can significantly delay seizure onset in these infants.…”
Section: Discussionmentioning
confidence: 99%
“…Presymptomatic treatment in tuberous sclerosis complex has been shown to improve seizure control and reduce the risk of intellectual disability 48 . Treatment during the presymptomatic phase in tuberous sclerosis complex sets precedence for presymptomatic treatment in other developmental epilepsy disorders, like SWS, where a high percentage of patients will have seizure onset in the first few years of life, and where early age of seizure onset has been repeatedly associated with worse neurological and developmental outcome 49–51 . More studies are needed to establish that presymptomatic treatment improves long‐term neurological and cognitive outcomes in SWS.…”
Section: Discussionmentioning
confidence: 99%
“…The location of tubers is quite heterogeneous, and a recent network analysis study showed that, while no single location was associated with the development of IESS, over 95% of tubers in patients with spasms had functional connectivity with the globi pallidi and cerebellar vermis [ 76 ]. Another mechanism involved in IESS pathophysiology in this patient population is abnormal GABAergic neurotransmission; previous studies have shown dysregulation of interneuron generation as well as a delay in the maturation of GABAergic networks [ 77 ]. Vigabatrin, a GABA–transaminase inhibitor, is known to be particularly efficacious in TSC patients; in addition to elevating brain GABA levels by inhibiting enzymatic degradation of this substrate, it also inhibits mTOR pathway activity specifically [ 77 ].…”
Section: Spectrum Of Genetic Aetiologies Of Iessmentioning
confidence: 99%
“…Another mechanism involved in IESS pathophysiology in this patient population is abnormal GABAergic neurotransmission; previous studies have shown dysregulation of interneuron generation as well as a delay in the maturation of GABAergic networks [ 77 ]. Vigabatrin, a GABA–transaminase inhibitor, is known to be particularly efficacious in TSC patients; in addition to elevating brain GABA levels by inhibiting enzymatic degradation of this substrate, it also inhibits mTOR pathway activity specifically [ 77 ].…”
Section: Spectrum Of Genetic Aetiologies Of Iessmentioning
confidence: 99%
See 1 more Smart Citation